2013
DOI: 10.1186/1750-1172-8-178
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal centrosome and spindle morphology in a patient with autosomal recessive primary microcephaly type 2 due to compound heterozygous WDR62 gene mutation

Abstract: BackgroundAutosomal recessive primary microcephaly (MCPH) is a rare neurodevelopmental disease with severe microcephaly at birth due to a pronounced reduction in brain volume and intellectual disability. Biallelic mutations in the WD repeat-containing protein 62 gene WDR62 are the genetic cause of MCPH2. However, the exact underlying pathomechanism of MCPH2 remains to be clarified.Methods/resultsWe characterized the clinical, radiological, and cellular features that add to the human MCPH2 phenotype. Exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 45 publications
5
41
0
Order By: Relevance
“…Previous studies on the intracellular distribution of ectopically expressed WDR62 with missense MCPH mutations that altered evolutionarily conserved residues revealed lost or substantially reduced spindle pole accumulation (Nicholas et al, 2010). Similar defects in spindle localization were also reported in primary cells isolated from an MCPH patient (Farag et al, 2013). MCPH-associated WDR62 mutants failed to rescue altered neuroprogenitor cell divisions induced by embryonic WDR62 depletion (Xu et al, 2014).…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies on the intracellular distribution of ectopically expressed WDR62 with missense MCPH mutations that altered evolutionarily conserved residues revealed lost or substantially reduced spindle pole accumulation (Nicholas et al, 2010). Similar defects in spindle localization were also reported in primary cells isolated from an MCPH patient (Farag et al, 2013). MCPH-associated WDR62 mutants failed to rescue altered neuroprogenitor cell divisions induced by embryonic WDR62 depletion (Xu et al, 2014).…”
Section: Introductionsupporting
confidence: 56%
“…Further experiments revealed an increased cellular proliferation by WDR62 overexpression and centrosome amplification by the concurrent overexpression of WDR62 and TPX2 in lung cancer cells and non‐cancerous bronchial epithelial cells for the first time. WDR62 is localized in the cytoplasm, including the centrosome, and mutant WDR62 causing primary microcephaly induced an abnormal centrosome . Moreover, the expression of both WDR62 and TPX2 led to AURKA activation in not only lung cancer cells in the present study, but also in uterine cervix cancer cells, and AURKA overexpression caused centrosome amplification in previous studies .…”
Section: Discussionsupporting
confidence: 67%
“…The human WDR62 ( WD repeat domain 62 ) gene is localized in the 19q13.12 region and encodes a 1523 amino acid protein that is localized in the cytoplasm and centrosome . WDR62 plays important roles in cell cycle progression, spindle maintenance, and cell proliferation, and germline mutations of the WDR62 gene cause primary microcephaly, which is characterized by a rare neurodevelopmental disease with severe microcephaly at birth . In human malignancies, the overexpression of WDR62 protein has been recently reported in gastric cancer and ovarian cancer; however, whether abnormal WDR62 expression is present in other types of cancers, including LAC, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…16,22,37 Analysis of patient-derived lymphocytes from an individual with compound heterozygous mutations that included the c.1313G>A (p.R438H) mutation revealed expression of missense mutant protein with defective mitotic localization. 37 This was consistent with the notion that a spindle localization deficit contributes to WDR62 pathomechanism and highlights the importance of mitotic specific functions in neurodevelopment. In co-immunoprecipitation studies we showed that interactions between AURKA and several MCPH-associated WDR62 mutants were compromised.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, AURKA interaction was not detected in complex with the WDR62 R438H mutant, one of the most commonly reported wdr62 MCPH mutations. 16,37 We extended our analysis to the AURKAdependent Ser49/Thr50 phosphorylation of WDR62 with MCPH-linked mutations. Assessment of the phosphorylation status of WDR62 Ser49/Thr50 using quantitative mass spectrometry revealed a 10.5-fold increase in phosphorylation in M-phase synchronized cells compared to S phase ( Figure 6B).…”
Section: Aurka Does Not Signal To Wdr62 Mcph Mutantsmentioning
confidence: 99%